Respostas
respondido por:
2
a
1/4.y² ( 10 - y)
Nota : 1/4 . y² = y²/4 ***
y²/4 ( 10 - y ) =
y²/4 * 10 = 10y²/4 ***
y²/4 * -y = y³/4 ****
reescrevendo
(10y²)/4 - ( y³/4 ) =
b
- 1/2 ( 2a - 8 )
- 1/2 * 2a = - 2/2 a = -1a ***
- 1/2 * -8 = +8/2 = 4 ***
reescrevendo
-a + 4 *** resposta
c
- 5m ( - 1,2 - 4/5.m )
-5m * - 1.2 = + 6m ***
-5m * - 4/5.m = + 20/5.m ou 4m ****
reescrevendo
6m + 4m = 10m **** resposta
d
x/6 ( x/2 - 6x² + 12 )
x/6 * x/2 = x²/12 ***
x/6 * - 6x² = - 6x³/6 = - x³ ***
x/6 * 12 = 12x/6 = 2x ***
reescrevendo
x²/12 - x³ + 2x **** resposta
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás